NFV deployment strategies in SDN network. (24th July 2019) - Tseng, Chia-Wei; Lai, Po-Hao; Huang, Bo-Sheng; Chou, Li-Der; Wu, Meng-Chiou
The emergence of the internet has resulted in the relative expansion of complicated network architecture. Accordingly, the traditional network architecture can no longer meet the demand of a new and rapidly changing network service. Given the emergence of software defined network (SDN) and network functions virtualisation (NFV), technologies can now transform the current and complicated network architecture into a programmable, virtualised and standardised managed architecture. This study aims to design and implement the rapid deployment strategies of the NFV services in SDN. Six different rapid deployment technologies are addressed based on the linked clone and the full clone cases. These technologies can accelerate the speed of deployment by enabling the NFV technology with an intelligent configuration. Experimental results show that the proposed parallel clone strategy in the linked clone scenario exhibited a better performance in terms of time efficiency compared with the other strategies.